Microbiome of Co-cultured Fish Exhibits Host Selection and Niche Differentiation at the Organ Scale - Zhang, Zhimin; Li, Dapeng; Xu, Weitong; Tang, Rong; Li, Li (Frontiers in Microbiology, 2019)
Fish are the most widespread aquaculture species and maintain complex associations with microbial consortiums. However, it remains elusive on the ecology of these associations present in multiple microhabitats in fish, especially on the microbial assembly in fish external (skin and gill) and internal (stomach and intestine) niches, and the relationship with the rearing environment. To understand host dependence and niches differentiation of organ-specific microbiome signatures using a 16S rRNA gene-based sequencing technique, we systematically provided characterizations of a comparative framework relevant the microbiome of stomach, regional intestine, skin and gill in two important farmed fish species, herbivorous grass carp (Ctenopharyngodon idellus) and carnivorous southern catfish (Silurus meridionalis), and of the rearing water. The different feeding habits of grass carp and southern catfish showed a significant separation of microbial community structure, with great compositional differences across body sites within each species. Sites-driven divergences relied on host species: the same types of microhabitats between grass carp and southern catfish harbored differential microbiome. Additionally, body sites had remarkably distinct communities and displayed lower alpha diversity compared to rearing water. Unexpectedly, the stomach of southern catfish had the highest microbial diversity in the digestive tract of the two co-cultured fish species. For external sites within each species, a higher diversity occurred in gill of grass carp and in skin of southern catfish. Our results unveil different topographical microbiome signatures of the co-cultured species, indicating host selection in individual-level microbial assemblages and niches differentiation at the organ scale. This work represents a foundation for understanding the comprehensive microbial ecology of cohabiting farmed fish, suggesting potential applications associated with fish microbiome that urgently needs to be assessed in poly-cultured operations in aquaculture.